Dynamics of nonthermal states in optimally doped B⁢i2⁢S⁢r2⁢C⁢a0.92⁢Y0.08⁢C⁢u2⁢O8+ẟ revealed by midinfrared three-pulse spectroscopy - Montanaro, Angela; Rigoni, Enrico Maria; Giusti, Francesca; Barba, Luisa; Chita, Giuseppe; Glerean, Filippo; Jarc, Giacomo; Mathengattil, Shahla Y.; Boschini, Fabio; Eisaki, Hiroshi; Greven, Martin; Damascelli, Andrea; et al. (Physical Review B, 2024)
In the cuprates, the opening of a d-wave superconducting (SC) gap is accompanied by a redistribution of spectral weight at energies two orders of magnitude larger than this gap. This indicates the importance to the pairing mechanism of on-site electronic excitations, such as orbital transitions or charge transfer excitations. Here, we resort to a three-pulse pump-probe scheme to study the broadband nonequilibrium dielectric function in optimally doped Bi2Sr2Ca0.92Y0.08Cu2O8+δ and we identify an interband excitation peaked at 2 eV whose spectral weight is transiently modified by the pump. Photoexcitation with near-infrared and midinfrared pulses, with photon energies, respectively, above and below the SC gap, reveals that the spectral weight dynamics is different for different pump wavelengths and depends on the time order of the two photoexcitations. The picture that emerges is that, while high-energy pulses excite quasiparticles in both nodal and thermally inaccessible antinodal states, photoexcitation by low-energy pulses mostly accelerates the condensate and creates excitations predominantly at the nodes of the SC gap. These results, rationalized by simulations based on the kinetic equations for d-wave superconducting gaps, indicate that dynamical control of the momentum-dependent distribution of nonthermal quasiparticles may be achieved by the selective tuning of the photoexcitation.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Dynamical phase transitions; Pairing mechanisms; Photoinduced effect; Ultrafast phenomena; Quantum many-body systems; Superconductivity; Drude model; Femtosecond laser spectroscopy; Optical pumping; Symmetries in condensed matter; Time-resolved infrared spectroscopy; Ultrafast pump-probe spectroscopy